Analysis of induction-based thermal demagnetization of a permanent magnet rotor in the context of recycling - Ihne, Thorsten; Wieprecht, Nico; Hahn, Roman; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference, 2023)
Rare Earth (RE) Magnets are a key for many green technologies causing continuously increasing demand in the European Union (EU). Alongside motors for e-mobility and generators in wind turbines, compressors in domestic heat pumps represent a potential lever for slowing climate change. On the other hand, the dominant market power of the PR China results in a high supply chain risk. Therefore, the EU has declared these elements as critical raw materials of the highest category and plans a compulsory recycling share of 15% until 2030. Currently, no systematic recycling activities for RE magnets are operated on an industrial scale. In the present paper a concept for the extraction of RE magnets from rotors of HVAC compressors is presented. The focus is set on the thermal in-situ demagnetization by induction which is crucial for the disassembly of the magnets. This process ensures efficient heating to temperatures above the individual Curie temperatures so that interfering reaction forces are eliminated. Systematic test series are carried out based on an experimental set-up to identify the main process parameters and restrictions. The achieved results are analyzed and are evaluated regarding the transferability to a potential series process.<br

Approaches For The Physical Sorting Of Soft And Hard Magnetic Material Mixtures In The Context Of Rare Earth Recycling - Ihne, Thorsten; Hahn, Roman; Kühl, Alexander; Franke, Jörg (Proceedings of the CPSL 2024., 2024)
Rare earth (RE) elements applied for magnets are considered as critical raw materials by most industrial countries. On the one hand especially neodymium-iron-boron (NdFeB) magnets are essential for the current economic transformation as they are used for core technologies such as electric mobility and wind power causing continuously increasing demand. On the other hand, there is a significant supply chain risk due to poor market diversification and bad substitutability. This leads to various economic problems such as steady rising prices, price volatility and potential shortages. In addition, the primary production has a poor ecological footprint. In this context, the recycling of NdFeB magnets has a high economic, geopolitical and ecological potential. However, hardly any recycling is currently carried out on industrial scale due to technical and organizational difficulties. As magnetic extraction from end-of-life (EOL) products by dismantling is only economically feasible in specific cases, the implementation of a universally applicable process based on shredding and multi-stage sorting is essential. Intensive research is currently being carried out for the further processing of the pure NdFeB granulate, but there is a lack of reliable separation processes for the hard and soft magnetic components of the ferrous shredding fraction, which are similar in terms of many physical properties. Therefore, the present paper discusses approaches based on physical sorting principles to close the existing gap in the overall process chain. The solution preferred by the authors is based on a multi-stage process chain realized as a flow process, which primarily exploits differences with regard to the mechanical and magnetic characteristics.<br
Keywords: Rare Earth Magnets; Critical Raw Materials; Recycling; Physical Sorting; Hard And Soft Magnetic Materials

Approach for Advanced Mechanical Recycling Strategies of Rare Earth Magnets Applied in Traction Drives - Ihne, Thorsten; Hahn, Roman; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (Production at the Leading Edge of Technology, 2023)
Rare Earth (RE) Magnets are crucial for the green transition of the European Union (EU). This applies especially for e-mobility where RE magnets are used for highly efficient traction drives. Permanent magnetic motors offer the best efficiency, but the use of Rare Earth Elements (REEs) is related to several drawbacks. The magnets and the required raw materials are almost exclusively imported. This causes problems for European industry due to supply chain risks and continuously increasing prices. In addition, primary production is associated with a poor ecological footprint. Therefore, the EU has declared REs as critical raw materials with highest supply chain risk and plans a compulsory recycling share of 15% until 2030. Currently, no industrially applicable processes exist for systematic recovery of RE magnets. In this context the following paper should present approaches for an automated process chain starting with an end-of-life traction drive until the extracted and demagnetized magnets.<br
Keywords: Rare earth magnets; Recycling; Traction drives; Critical raw materials

Approach For Optimized Dismantling Strategies And Design For Recycling Of Electric Traction Drives - Hahn, Roman; Wieprecht, Nico; Ihne, Thorsten; Kühl, Alexander; Franke, Jörg (6th Conference on Production Systems and Logistics, 2024)
With the widespread adoption of electric vehicles (EVs), there arises a pressing need for sustainable processing of electric traction drives (ETDs) at the end of their life cycles. Current methods for dismantling and recycling ETDs often show inefficiencies in material recovery causing economic disadvantages and increased environmental impact. Of particular relevance is the recycling of rare earth (RE) magnets, which are extensively used in ETDs because of their superior magnetic properties. Given the scarcity of rare earth elements (REEs) and the environmental impact associated with their extraction, the need for efficient RE magnet recycling is of key importance. However, there is currently a lack of efficient dismantling processes and recyclability is often inadequate. By developing an optimized approach that focuses on adapted dismantling strategies and design for recycling, a critical gap in the sustainable production and disposal of electric vehicles will be closed. A crucial aspect is the design for recycling, enabling efficient recovery and reuse of materials and components. The approach presented in this paper combines different aspects such as material composition, modularity of components, standardization and good separability to optimize the design for recycling of ETDs. By providing optimized dismantling strategies as well as guidelines for the design for recycling, the transition to more environmentally sustainable transport systems is supported in addition to increased economic efficiency. <br
Keywords: Recycling; Reuse; Optimized Dismantling; Design for Recycling; Electric Traction Drives; Rare Earth Magnets; Permanent Magnet Synchronous Machine

Electric Propulsion Units in aviation - approach for a mechanical permanent magnet rotor design and the related manufacturing concept - von Lindenfels, Johannes; Ihne, Thorsten; Franke, Jörg; Kühl, Alexander (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
Electric propulsion units are key components for hybridization and electrification of aviation enabling decarbonization and emission reduction. This application is characterized by significant requirements regarding reliability and power density. This paper deals with a specific mechanical rotor design for Electric Propulsion Units configured as Halbach array and its related manufacturing process. First, existing rotor configurations of electric propulsion units are discussed. Based on this analysis optimization potentials regarding air gap minimization, cooling and retaining of centrifugal forces are introduced. The derived reference design compromises a modular setup of the magnetic active part including combinations of form fit and adhesive bond for all relevant interfaces. The individual advantages and disadvantages of the design as well as further optimization potentials are evaluated based on simulative and experimental investigations. The selected design correlates with a specific assembling and magnetization process which is also discussed. Due to a high number of single parts the assembling is performed as multistage process. The magnetization is conducted applying a sub-assembly strategy to avoid manufacturing problems. Finally, an outlook is given with focus set on the aviation compliant certification process.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric motor production; Electric Propulsion Units; Halbach Array; sub-assembly magnetization

Functionally integrated additive manufactured rotor components for torque-dense aircraft electric motors - von Lindenfels, Johannes; Posch, Dennis; Ihne, Thorsten; Franke, Jörg; Kühl, Alexander (Procedia CIRP, 2023)
In dealing with emissions targets worldwide, fundamental questions about the future arise for commercial aviation. The resulting consequences for aviation require efforts to make air traffic CO2 neutral. In this context, electrification is an important building block to enable the aviation industry to provide transport in the future with increasing traffic volumes. To achieve this goal, electric motors for flight operation must have a high power and torque density and operate as energy-efficiently as possible. The PM synchronous motors predominantly proposed for such applications have above average efficiencies but could provide higher peak powers if they could be thermally more loaded. In particular, the sensitive permanent magnets lose efficiency as the operating temperature of the electric motor increases, reducing the maximum possible torque of the motor. Since conventional rotor construction methods limit the design, additive manufacturing is used to develop a rotor design that allows the rotor magnets to be cooled in close range to their contours. In addition, by selective laser melting mechanical, thermal, and magnetic functions are integrated. A process for hybrid manufacturing of novel rotor topologies is proposed. For this purpose, the rather conventional rotor topology is replaced by an additive function-integrated component for a reference electric motor. By means of an FEM analysis, it was shown that the mechanical strength of the alternative fixation method is maintained. Using adequate design guidelines, the AM structural components were fabricated in aluminum and an iron-nickel alloy and the permanent magnets were secured on it using 1K-epoxy adhesive. CFD analysis was used to simulate the flow conditions and heat transfer to the coolant in the internal structures of the AM components. Finally, the effect of the integrated cooling function was verified with an experimental setup. The results show that the torque influencing factor of the magnetic induction can be increased.<br
Keywords: Additive manufacturing; PMSM; Electric aviation; Magnetics; cooling system; Halbach array

Recycling Concept for Electric Vehicle Drives in the Context of Rare Earth Recovery - Ihne, Thorsten; Hahn, Roman; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Neodymium Iron Boron (NdFeB) magnets provide the best magnetic properties and are therefore key components for many green technologies. This leads to steeply rising demand for the related rare earth (RE) elements, with e-mobility as central driver. The supply situation for RE magnets is characterized by the dominance of the PR China for the entire value chain causing various problems for the European industry. A potential countermeasure to reduce the dependency on imports is the implementation of a closed raw material cycle within the European Union (EU). Especially the recycling of automotive traction drives provides high potential for the recovery of RE magnets but is complicated by various technical and organizational factors. As result currently no recycling is industrialized for the recovery of RE magnets from traction drives of end-of-life (EOL) electric vehicles (EV).In this context the following paper presents a general concept for the recovery of RE magnets from automotive traction motors. The focus is set on the extraction process of the magnets from the rotor and the related thermal demagnetization step. Finally, the achieved results are evaluated regarding the transferability to a potential series process.<br
Keywords: Electric potential; Europe; Rotors; Electric vehicles; Traction motors; Recycling; Magnets; Rare earth magnets; circular economy; recycling; electromobility; traction drives; thermal demagnetization

The Power of Technological Innovation - Franke, Jörg; Wasserscheid, Peter; Ihne, Thorsten; Lamp, Peter; Guldner, Jürgen; Zipse, Oliver (Road to Net Zero, 2023)
Achieving the urgent need for rapid decarbonization to meet the 1.5 °C target requires disruptive technological change. In the automotive industry, technological progress is closely linked to improved sustainability, and sustainability goals drive the need for technological innovation. However, new technologies in the mobility sector are fraught with uncertainties that challenge both original equipment manufacturers (OEMs) and their stakeholders, such as suppliers, customers, and policy-makers. Therefore, this chapter focuses on the technical, economic, and environmental evaluation of alternative powertrain concepts and the management of uncertainties associated with emerging technological innovation as part of the broader transition to net zero. Electric mobility plays a central role in the sustainability transition and is characterized by a high degree of variance. Battery electric vehicles (BEVs) are expected to dominate private transport in the future due to their greenhouse gas and pollutant-free operation and high efficiency. In addition to charging infrastructure, the technical challenges currently lie primarily in cell chemistry and power electronics. Advances in battery technology and infrastructure electrification will help eliminate the range problem in the future. Another important future fuel is hydrogen. One application is the fuel cell vehicle, which combines the advantages of a chemical energy carrier with high gravimetric energy density with those of an electrical energy converter. Hydrogen also plays an important role as an energy carrier for specific energy supply processes in manufacturing processes and simplifies the transport of regeneratively generated energy. In addition, hybrid vehicles are a transitional technology, and alternative fuel internal combustion engines can contribute to the decarbonization of the existing fleet and to specific applications. This chapter assesses the performance of alternative powertrains; highlights the interrelationship between powertrain systems, energy ecosystems, and sustainability goals; and identifies future research directions for electric and hydrogen mobilit
Keywords: Electromobility; Hydrogen mobility; Alternative powertrains; Energy ecosystem; Battery technology; Charging technology